Kinetics and Statistical Analysis in Biogas Production: Optimization of Clostridium welchii Bioaugmentation of Solid Organic Waste from Shinko - Yusufu Luka; Abdulhalim Musa Abubakar; Hassan Ahmed Saddiq; David Ufedo Apeh (Scientific Journal of Engineering Research, 2026)
Natural microbial communities in cassava peel (CP), sugarcane waste (SW), and poultry manure (PM) are often inadequate to sustain stable anaerobic digestion (AD) for efficient biogas production. This study employed bioaugmentation with Clostridium welchii to improve process stability and biogas production, thereby promoting the valorization of organic wastes generated in Shinko, Adamawa State. CP, SW, and PM were codigested at a 5:4:1 ratio under three conditions: a non-bioaugmented control (X) and two bioaugmented setups (Y and Z) containing 200 and 300 mL of Clostridium welchii, respectively. Biogas production over a 40-day digestion period was fitted to the Modified Gompertz, Cone, Fitzhugh, and Logistic kinetic models to estimate kinetic parameters. Model performance across the three bioreactor setups was evaluated using 29 statistical metrics. The maximum experimental biogas yields at day 40 were 1.19, 2.13, and 1.85 m3/kg for X, Y, and Z, respectively, with predicted values showing close agreement. Among all models, the Modified Gompertz model for setup Y demonstrated the best overall performance, combining the highest biogas yield, the fastest production rate (k), favorable shape factor (n), a short lag phase, and excellent statistical agreement (R2 > 0.9992). Bioaugmentation with 200 mL of Clostridium welchii proved the most efficient and stable strategy for codigesting CP, SW, and PM based on all 29 statistical criteria. Overall model performance ranked as Modified Gompertz > Cone > Logistic > Fitzhugh. Moderate bioaugmentation optimized microbial activity, shortened the lag phase, increased biogas production rates, and strengthened the predictive accuracy of the kinetic models.